Improved outcome of patients with graft-versus-host disease after allogeneic hematopoietic cell transplantation for hematologic malignancies over time: an EBMT mega-file study - Greinix, Hildegard T.; Eikema, Dirk-Jan; Koster, Linda; Penack, Olaf; Yakoub-Agha, Ibrahim; Montoto, Silvia; Chabannon, Christian; Styczynski, Jan; Nagler, Arnon; Robin, Marie; Robinson, Stephen; Chalandon, Yves; et al. (Haematologica, 2022)
Acute graft-versus-host disease (aGvHD) remains a major threat to successful outcome following allogeneic hematopoietic cell transplantation though advances in prophylaxis and supportive care have been made. The aim of this study is to test whether the incidence and mortality of aGvHD have decreased over time. 102,557 patients with a median age of 47.6 years and with malignancies after first allogeneic sibling or unrelated donor (URD) transplant were studied in the following periods: 1990-1995, 1996-2000, 2001-2005, 2006-2010 and 2011-2015. Findings: 100-day incidences of aGvHD grades II-IV decreased from 40% to 38%, 32%, 29% and 28%, respectively, over calendar time (P<0.001). In multivariate analysis URD, not in complete remission (CR) at transplant or untreated, and female donor for male recipient were factors associated with increased risk whereas the use of ATG/alemtuzumab decreased aGvHD incidence. Median follow-up was 214, 169, 127, 81 and 30 months, respectively, for the periods analyzed. Three-year-survival after aGvHD grades II-IV increased significantly from 38% to 40%, 43%, 44%, and 45%, respectively. In multivariate analysis URD, not in CR at transplant, peripheral blood as stem cell source, female donor for male recipient, and the use of ATG/alemtuzumab were associated with increased mortality whereas reduced-intensity conditioning was linked to lower mortality. Mortality increased with increasing patient age but decreased in the recent cohorts. Our analysis demonstrates that aGvHD has decreased over recent decades and also that the survival rates of patients affected with aGvHD has improved.